2002
DOI: 10.1002/mpo.10212
|View full text |Cite
|
Sign up to set email alerts
|

Localised Ewing sarcoma/PNET of bone—prognostic factors and international data comparison

Abstract: Overall survival progressively improved. From 1994 to 1998 the survival of patients with small tumors and/or favorable sites was similar to the best reported results. It was not possible to compare results by tumor size for large tumors, > 500 ml, due to the absence of data from elsewhere. A better staging system is required for the international comparison of results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…These characteristics include age, primary tumor location and size, the presence or absence of metastases, the serum lactate dehydrogenase level, and the response to therapy (Bacci et al 2000;Catterill et al 2000;Obata et al 2007;Rodriguez-Galindo et al 2003;Sluga et al 2001). Although chemotherapeutic regimens and treatment strategies based on prognostic factors have been advanced, previous reports from developing countries indicate that similar results were not obtained in non-western population (Cardenas-Cardos et al 1999;Jenkin et al 2002;Villarroel et al 1997) Thus, previously reported prognostic factors may not have the same inXuence on clinical outcome in patients belonging to populations with a low incidence, even if developed countries.…”
Section: Introductionmentioning
confidence: 95%
“…These characteristics include age, primary tumor location and size, the presence or absence of metastases, the serum lactate dehydrogenase level, and the response to therapy (Bacci et al 2000;Catterill et al 2000;Obata et al 2007;Rodriguez-Galindo et al 2003;Sluga et al 2001). Although chemotherapeutic regimens and treatment strategies based on prognostic factors have been advanced, previous reports from developing countries indicate that similar results were not obtained in non-western population (Cardenas-Cardos et al 1999;Jenkin et al 2002;Villarroel et al 1997) Thus, previously reported prognostic factors may not have the same inXuence on clinical outcome in patients belonging to populations with a low incidence, even if developed countries.…”
Section: Introductionmentioning
confidence: 95%
“…Improvements in diagnosis and chemotherapy treatment of PNET have led to a prolonged survival [1]. This emphases the importance of facilitating operative reconstruction and enabling normal growth in these children post therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Prognosis of ET remains poor, with 5-year relapse-free survival of 55 to 65% in patients with localised disease and not exceeding 25% in primary metastatic disease. Survival at 5 years after relapse is less than 20% (Cotterill et al, 2000;Paulussen et al, 2001;Jenkin et al, 2002).…”
mentioning
confidence: 97%
“…In ET, prognostic factors include age, primary site, and tumour volume, the presence of metastases at diagnosis detected by conventional methods and histological response to induction chemotherapy (Cotterill et al, 2000;Paulussen et al, 2001;Jenkin et al, 2002). Bone marrow micrometastases and circulating tumour cells detected by RT -PCR were also recently reported as prognostic factors (Schleiermacher et al, 2003).…”
mentioning
confidence: 99%